Employee Performance Improvement Strategy at Pelita Abadi Motor Tangerang - Nur Azis; Aries Sundoro; Achmad Mulyana; Choerul Fakih; Wulandari; Lesna Purnawan (The International Journal of Education Management and Sociology, 2025)
This study aims to assess the employee performance at Cahaya Abadi Motor Tangerang. The research findings indicate that the improvement of employee performance at PT Cahaya Abadi Motor Tangerang is achieved through providing training and education to employees. The main factors influencing employee performance are the implementation of discipline and the provision of motivation. This research is a field study. In terms of data type, this research uses a qualitative research method. The data utilized consists of primary and secondary data. Primary data was obtained from observations and interviews, while secondary data was gathered from written sources, both online and in libraries. The research results show that employee discipline can be assessed through attendance, adherence to rules, responsibility for assigned tasks, attention to detail in work, and polite behavior in the workplace. Meanwhile, work motivation can be enhanced by increasing employee wages, providing recognition for employees, and offering comfortable facilities and a conducive work environment. Overall, the improvement of employee performance at PT Cahaya Abadi Motor Tangerang is quite satisfactory. The training and education programs, the implementation of discipline, and the provision of motivation in the form of rewards, along with a comfortable and conducive work environment, have proven effective in enhancing the performance of employees at PT Cahaya Abadi Motor Tangerang.